Compassionate Use of Hydroxychloroquine in Clinical Practice for Patients With Mild to Severe COVID-19 in a French University Hospital. (18th June 2020) - Paccoud, Olivier; Tubach, Florence; Baptiste, Amandine; Bleibtreu, Alexandre; Hajage, David; Monsel, Gentiane; Tebano, Gianpiero; Boutolleau, David; Klement, Elise; Godefroy, Nagisa; Palich, Romain; Itani, Oula; et al.
Abstract: Background: Data from nonrandomized studies have suggested that hydroxychloroquine could be an effective therapeutic agent against coronavirus disease 2019 (COVID-19). Methods: We conducted an observational, retrospective cohort study involving hospitalized adult patients with confirmed, mild to severe COVID-19 in a French university hospital. Patients who received hydroxychloroquine (200 mg 3 times daily dosage for 10 days) on a compassionate basis in addition to standard of care (SOC) were compared with patients without contraindications to hydroxychloroquine who received SOC alone. A propensity score-weighted analysis was performed to control for confounders: age, sex, time between symptom onset and admission ≤ 7 days, Charlson comorbidity index, medical history of arterial hypertension, obesity, National Early Warning Score 2 (NEWS2) score at admission, and pneumonia severity. The primary endpoint was time to unfavorable outcome, defined as: death, admission to an intensive care unit, or decision to withdraw or withhold life-sustaining treatments, whichever came first. Results: Data from 89 patients with laboratory-confirmed COVID-19 were analyzed, 84 of whom were considered in the primary analysis; 38 patients treated with hydroxychloroquine and 46 patients treated with SOC alone. At admission, the mean age of patients was 66 years, the median Charlson comorbidity index was 3, and the median NEWS2 severity score was 3. After propensity score weighting, treatment with hydroxychloroquine was not associated with a significantly reduced risk of unfavorable outcome (hazard ratio, 0.90 [95% confidence interval, .38–2.1], P  = .81). Overall survival was not significantly different between the 2 groups (hazard ratio, 0.89 [0.23; 3.47], P  = 1). Conclusion: In hospitalized adults with COVID-19, no significant reduction of the risk of unfavorable outcomes was observed with hydroxychloroquine in comparison to SOC. Unmeasured confounders may have persisted however, despite careful propensity-weighted analysis and the study might be underpowered. Ongoing controlled trials in patients with varying degrees of initial severity on a larger scale will help determine whether there is a place for hydroxychloroquine in the treatment of COVID-19. In hospitalized adults with COVID-19, no significant reduction of the risk of unfavorable outcomes was observed with hydroxychloroquine in comparison to SOC. Abstract : In hospitalized adults with Covid-19, no significant reduction of the risk of unfavorable outcomes was observed with hydroxychloroquine in comparison to standard of care.